Quantification of hydraulic redistribution in maize roots using neutron radiography - Hayat, F (2021)
We show how to use neutron radiography to quantify the rate of water efflux from the roots to the soil. Maize (Zea mays L.) plants were grown in a sandy substrate 40 cm deep. Deuterated water (D2O) was injected in the bottom wet compartment, and its transport through the roots to the top dry soil was imaged using neutron radiography. A diffusion–convection model was used to simulate the transport of D2O in soil and root and inversely estimate the convective fluxes. Overnight, D2O appeared in nodal and lateral roots in the top compartment. By inverse modeling, we estimated an efflux from lateral roots into the dry soil equal to jr = 2.35 × 10−7 cm−1. A significant fraction of the redistributed water flew toward the tips of nodal roots (3.85 × 10−8 cm3 s−1 per root) to sustain their growth. The efflux from nodal roots depended on the roots’ length and growth rate. In summary, neutron imaging was successfully used to quantify hydraulic redistribution. A numerical model was needed to differentiate the effects of diffusion and convection. The highly resolved images showed the spatial heterogeneity of hydraulic redistribution.